Gold fever [large type] - Cole, Tobias (The Sharpshooter, 2019)
"GOLD FEVER Union Army sharpshooter Jed Wells met the possibly mad artist Josephus McCade when they were prisoners in Andersonville, and he remembers well the strange man's rants about a "key" to unimaginable wealth. Now that the guns of the war between North and South have fallen forever silent, curiosity is drawing Jed back onto the trail of the eccentric McCade. But the artist's charmed life may soon be coming to a brutal end, thanks to a secret he will tell no one--a mystery that's pulling Jed Wells himself into the gunsight of a killer. ("--